Management strategy for management of independent practice nursing in Badung District, Bali Province, Indonesia - ., Taukhit (International Journal Of Community Medicine And Public Health, 2020)
Background: Nurses have the authority to open an independent practice of nursing as one of the health services. But in reality, not all nurses can implement management strategies independently of nursing practice well to support the progress of practice. The purpose of this study was to conduct an in-depth analysis of nurses’ experiences in conducting management strategies in opening independent nursing practices in Badung Regency, Bali Province. Methods: The study used a qualitative method with a phenomenological approach. The main informants consisted of nine nurses who owned independent nursing practices. The triangulation informant was from the chairperson of the Indonesian national nurse’s association of Badung regency and three patients. Data analysis uses the fixed comparison method according to Glaser and Strauss. Results: Research shows strategies in managing independent nursing practice management include planning for strategic place selection, organizing structured services, planning for providing facilities and managing personnel. At the implementation stage of the service strategy formulation includes promotive, preventive and complementary treatment activities. The most effective service introduction through word of mouth marketing. At the quality control stage through increased competence and service improvement. The development of practices is planned to be a joint practice, hospitalization, an independent practice training center and a clinical practice place for nursing students. Conclusions: The independent nursing practice management strategy was carried out at the preparation, implementation and control stages of the independent nursing practice management formulation.